Hubungan Diabetes Self-Management Dengan Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 di RS Amelia Pare Kediri - Laili, Nurul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Diabetes self management require compliance with complex management regimens to achieve glycemic control. Management of diabetes mellitus begins with the setting of food, physical exercise, weight control and optimal adjustment of medication. Treatment of diabetes mellitus to improve the quality of life of patients and prevent complications makrovasculer and mikrovasculer. The purpose of this research is to identify the relationship of diabetes self-management to the quality of life of patients with diabetes mellitus type 2. The design used in this study was cross sectional. The population in this study were all patients with diabetes mellitus type 2. The sample in this study are patients with diabetes mellitus type 2 who came controls on poli Amelia Pare Hospital in September 2016. The analysis performed in this study using Spearman Rank Correlation. Obtained value of Rho = 0.33 which indicates the level of relationship is. Statistical test value t = 7.23 is greater than t table = 2.457, then Hâ‚ acceptable and it can be concluded that there is a relationship between diabetes self-management and quality of life mellitus type 2 diabetes patients with a degree of closeness of the relationship that is being nurses in providing nursing care also pay attention to the patient's needs will be perceptions about the treatment. Nurses as educators can provide explanations and correct health information about treatment and care so that quality of life can be achieved.Â Keyword: Diabetes Self-Management, Quality of life, Diabetes Mellitus tipe 2